Implementation Of Online-Based Health Sports Education Learning For High School Students - Kurniawan, Ari Wibowo; Nadhifah, Yufa Fajrin (Journal Coaching Education Sports, 2022)
The purpose of this study was to determine the learning of courage in SMA Negeri 1 Kejayan. The author wants to know and conduct research on the courageous learning of class X students of SMAN 1 Kejayan. This research uses a survey method. The number of samples in this study was 103 people which were calculated using the error tolerance limit formula (error tolerance). The data collection technique used is a questionnaire that is packaged into a google form. The data analysis technique used was using percentage analysis which was calculated using Microsoft Excel. The results of this study indicate that bold learning in SMAN 1 Kejayaan students has difficulty practicing in PJOK subjects, this is because PJOK subjects apply more direct practice while learning is limited to watching videos. The results of this study with answers as many as 76 respondents (94%) answered strongly agree that they have difficulty in learning PJOK bravely. It is hoped that teachers can make learning materials more interesting and can make it easier for students to take part in learning boldly. These results are expected to be a reference for teachers to make bold learning models that are more interesting.